Research on emotional schemas: A review of findings and challenges. (8th September 2018) - Edwards, Emily R.; Wupperman, Peggilee
Abstract: Background: In recent years, the field of emotion research has seen a marked increase in theories and studies of emotional schemas—core beliefs about emotions and emotional experiences. This review serves to organise this growing body of literature, particularly as it relates to clinical practice. Methods: The review focuses specifically on literature relevant to emotional schema conceptualisation, aetiology and development, and relation to psychoemotional functioning. Pervasive limitations of past research are highlighted and areas needing further empirical attention are identified. Results: Growing evidence attests to the potential clinical implications of emotional schemas. However empirical advancement in this area is impeded by limited theoretical and operational integration across research. Conclusions: Through strategic research, the field could begin to build a more universal theoretical framework of emotional schemas. This would greatly improve our ability to research, understand, and therapeutically target a construct that may underlie a broad range of psychopathology.